A multiscale simulation framework of the accumulative roll bonding process accounting for texture evolution - Prakash, Aruna; Nöhring, Wolfram Georg; Lebensohn, R. A.; Höppel, Heinz Werner; Bitzek, Erik (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2015)
The accumulative roll bonding process is one of the most prominent severe plastic deformation processes for obtaining sheet materials with ultra-fine-grained microstructures and high strength. The properties of such sheets differ significantly from those of conventionally rolled sheets. It is hence desirable to have a simulation framework that can accurately predict the material properties, including the evolving texture and anisotropy during processing. Here, we propose such a framework for multiple pass rolling using explicit finite elements and embedding the visco-plastic self-consistent (VPSC) polycrystal texture model for the material response. To facilitate multiple pass rolling, we propose a novel solution mapping scheme that transfers the material state from the deformed finite element mesh to a new one. Additionally, we implement a two-level parallelization scheme – with decomposition of the FE domain using message passing interface (MPI) and thread based parallelization of the material response using OPENMP – to ensure reduced simulation times. The predictive capabilities of the proposed framework are demonstrated by simulating the accumulative roll bonding of aluminum alloy AA5754 sheets. The simulations validate the working of the solution mapping scheme, and clearly show the development of a through thickness gradient of texture and anisotropy in the roll-bonded sheet after two passes.
WW1::1018

Atomistic Model Analysis of Local and Global Instabilities in Crystals at Finite Temperature - Umeno, Yoshitaka; Nöhring, Wolfram Georg; Iskandarov, Albert; Bitzek, Erik (Key Engineering Materials, 2013)

Atomistic model analysis of local and global instabilities in crystals at finite temperature - Umeno, Yoshitaka; Nöhring, Wolfram Georg; Iskandarov, Albert; Bitzek, Erik (Key Engineering Materials, 2014)
WW1::985

Wedge-shaped twins and pseudoelasticity in fcc metallic nanowires under bending - Nöhring, Wolfram Georg; Möller, Johannes; Xie, Zhuocheng; Bitzek, Erik (Extreme Mechanics Letters, 2016)
WW1::1079
Keywords: Simulation and Modeling